THE MATHEMATICAL APPROACH OF THE ASSESSMENT OF ECOLOGICAL RISKS ON THE EXAMPLE OF TOXINS - Петрусенко, Валентина Павлівна; Дмитруха, Тетяна Іллівна (Science-based technologies, 2019)
The article analyses the actual research and the meaning of assessment of ecological risks on the example of a non-threshold toxins. This question is very urgent from the point of using of a great amount of harmful substances, which get into the environmental and as a result into the food links, the users of which is a man. In this study it is examined the results of negative influence carcinogens on the health on the example vinyl chloride, arsenic, dioxins, which get into the organism of man via the using of water, polluted by these toxins. The article gives a short characteristic of selected harmful substances the main sources and the ways of getting into the environment and to the organism of man. To define certain risks, it was taken into consideration corresponding suitable, factors of risks, permissible concentration of carcinogens in the water, the rate of getting water into the organism of man, average time of possible harmful influence. On the basis of done calculations it was determined that the most amount of dioxins can get with water and the least amount of arsenic, the main risk for the mans health gives vinyl chloride. More over it exceeds the volume of permissible risk <!--[if gte vml 1]> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if gte mso 9]> <![endif]-->, which is rather dangerous for the person health. At present it is observed the simultaneous availability of many carcinogens both in air and in water. So it was examined the additive model of accounting of risks that foresees the consideration of some harmful factors. But the negative impact and available risks can be not only added but they can intensify a harmful influence of one factor on another. In this case it is observed such a phenomenon as a synergism, that also must be taken into consideration while calculating the risks. That′s why calculating such risks a coefficient of synergism was used. The study found out that the content carcinogens in water can be rather dangerous. The most danger is the content of dioxins in water in spite of the fact that they dissolve in water very bad. The article analyses the actual research and the meaning of assessment of ecological risks on the example of a non-threshold toxins. This question is very urgent from the point of using of a great amount of harmful substances, which get into the environmental and as a result into the food links, the users of which is a man. In this study it is examined the results of negative influence carcinogens on the health on the example vinyl chloride, arsenic, dioxins, which get into the organism of man via the using of water, polluted by these toxins. The article gives a short characteristic of selected harmful substances the main sources and the ways of getting into the environment and to the organism of man. To define certain risks, it was taken into consideration corresponding suitable, factors of risks, permissible concentration of carcinogens in the water, the rate of getting water into the organism of man, average time of possible harmful influence. On the basis of done calculations it was determined that the most amount of dioxins can get with water and the least amount of arsenic, the main risk for the mans health gives vinyl chloride. More over it exceeds the volume of permissible risk <!--[if gte vml 1]> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if gte mso 9]> <![endif]-->, which is rather dangerous for the person health. At present it is observed the simultaneous availability of many carcinogens both in air and in water. So it was examined the additive model of accounting of risks that foresees the consideration of some harmful factors. But the negative impact and available risks can be not only added but they can intensify a harmful influence of one factor on another. In this case it is observed such a phenomenon as a synergism, that also must be taken into consideration while calculating the risks. That′s why calculating such risks a coefficient of synergism was used. The study found out that the content carcinogens in water can be rather dangerous. The most danger is the content of dioxins in water in spite of the fact that they dissolve in water very bad.